Relationship of vasculogenic mimicry, SphK1 expression, and Cx43 expression to metastasis and prognosis in colorectal cancer - Su, Ying-Jie (Int J Clin Exp Pathol, 2018)
Objective: To determine the presence of vasculogenic mimicry (VM) and expression of Sphingosine kinase 1 (SphK1) and Connexin43 (Cx43) in colorectal cancer (CRC) tissues, and to identify their inter-relationships and associations with multiple pathologic parameters. Methods: Ninety-two CRC specimens and normal pericarcinoma tissues were analyzed for expression of SphK1 and Cx43 using immunohistochemistry, and for identification of VM using CD34-periodic acid-Schiff dual staining. Results: The positive rate of SphK1 expression was greater in CRC cells than pericarcinoma cells (85.87% vs. 33.70%, P < 0.05). In contrast, the positive rate of Cx43 expression was greater in pericarcinoma cells than in CRC cells (58.70% vs. 92.39%, P < 0.05). Analysis of CRC tissues indicated that expression of SphK1 was associated with poor differentiation, advanced tumor stage, lymph node metastasis, and the presence of VM (P < 0.05 for each comparison). Expression of Cx43 was associated with high differentiation and the presence of VM (P < 0.05 for each comparison). Patient sex, age, tumor size, depth of invasion, and distant metastasis were unrelated to the expression of either protein. There was a significant correlation between the expression of SphK1 and Cx43 (P < 0.05). Analysis of overall patient survival indicated that SphK1 positivity and the presence of VM were significantly associated with poor survival, but Cx43 positivity had no relationship with survival. Conclusion: SphK1 protein expression was significantly greater in CRC tissues than pericarcinoma tissues, suggesting this protein may be associated with the pathogenesis of CRC. In addition, the significant correlation between expression of SphK1 and Cx43 in CRC tissues suggests their interaction may impact the pathogenesis of CRC.